Collagen VI in healthy and diseased nervous system - Ilaria Gregorio; Paola Braghetta; Paolo Bonaldo; Matilde Cescon (The Company of Biologists, 2018)
Collagen VI is a major extracellular matrix protein exerting a number of functions in different tissues, spanning from biomechanical to regulatory signals in the cell survival processes, and playing key roles in maintaining the stemness or determining the differentiation of several types of cells. In the last couple of years, emerging findings on collagen VI have led to increased interest in its role in the nervous system. The role of this protein in the peripheral nervous system was intensely studied and characterized in detail. Collagen VI acts as a regulator of Schwann cell differentiation and is required for preserving peripheral nerve myelination, function and structure, as well as for orchestrating nerve regeneration after injury. Although the role and distribution of collagen VI in the peripheral nervous system is now well established, the role of this distinctive extracellular matrix component in the central nervous system, along with its links to human neurological and neurodegenerative disorders, remains an open field of investigation. In this Review, we summarize and discuss a number of recent findings related to collagen VI in the central and peripheral nervous systems. We further link these findings to different aspects of the protein that are relevant to human diseases in these compartments in order to provide a comprehensive overview of the roles of this key matrix component in the nervous system.